Cloning Sheep Cytokin Genes and Preliminary Transfect to HT29 Cell Line - Sang, Vu Van; Andronicos, Nicholas (VNU Journal of Science: Natural Sciences and Technology, 2024)
The study was carried out to clone sheep cytokine genes for protein expression in mammalian cell culture. Once expressed it is hypothesized that these proteins when added to a primary mast cell culture will allow the growth of these cells. Mast cells are used by sheep to combat gastro-intestinal nematode (GIN) by helping to establish the host immune response and to eliminate of GIN. Kit ligand and IL3 proteins are growth factors of mast cells that were derived from extraction of total RNA from lung and thymus tissues, respectively. The IL3 and kit ligand genes were cloned into bacterial expression pGEM – T easy vector to determine correct sequences before being sub-cloned into the mammalian expression pWPI vector. The Pac 1 enzyme was used to cut restriction sites of pGEM – T easy vector, pWPI vector, IL3 and kit ligand genes in cloning strategies. The study also established 24 different conditions for transient transfection IL3 and Kit ligand genes into HT29 cells and screen positive cells on the flow cytometry. Results showed that clones of IL3 and kit ligand with the correct sequences were created for using transient transfection. The transfection efficiency of IL3 and kit ligand DNA/ pWPI plasmid into HT29 cells were extremely low with approximately 9% for the best condition. This low transfection efficiency leads to shortage of IL3 and kit ligand for growing mast cells. Therefore, stable transfection will be required to have highest efficiencies that produce the large quantities of IL3 and kit ligand proteins required for culture of sheep mast cell lines.